2010
DOI: 10.1128/aac.00756-09
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Proteome of Candida albicans in Response to Azole, Polyene, and Echinocandin Antifungal Agents

Abstract: The yeast Candida albicans is an opportunistic human fungal pathogen and the cause of superficial and systemic infections in immunocompromised patients. The classes of antifungal agents most commonly used to treat Candida infections are the azoles, polyenes, and echinocandins. In the present study, we identified changes in C. albicans protein abundance using two-dimensional polyacrylamide gel electrophoresis and matrix-assisted laser desorption ionization-time of flight mass spectroscopy following exposure to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
72
2
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(91 citation statements)
references
References 55 publications
11
72
2
5
Order By: Relevance
“…Adicionalmente, la candidiasis oral y orofaríngea (7,8), son las infecciones fúngicas más comunes en pacientes oncológicos sometidos a tratamiento antineoplásico; paciente con grandes estadías hospitalaria (9), también se encuentra presente en algunos estados fisiológicos como enfermedades metabóli-cas, endocrinopatías, síndrome de inmunodeficiencia adquirida, uso de medicamentos, intervenciones quirúrgicas, en donde se pueden presentar posibles fallas en los tratamientos instaurados con antimicó-ticos, adquiriendo resistencia (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Adicionalmente, la candidiasis oral y orofaríngea (7,8), son las infecciones fúngicas más comunes en pacientes oncológicos sometidos a tratamiento antineoplásico; paciente con grandes estadías hospitalaria (9), también se encuentra presente en algunos estados fisiológicos como enfermedades metabóli-cas, endocrinopatías, síndrome de inmunodeficiencia adquirida, uso de medicamentos, intervenciones quirúrgicas, en donde se pueden presentar posibles fallas en los tratamientos instaurados con antimicó-ticos, adquiriendo resistencia (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Introductionunclassified
“…Actualmente se ha visto este hongo, también implicado en procesos de resistencia a sustancias anti fúngicas ya existentes (10)(11)(12), razón por la que se considera de gran importancia la investigación en productos que inhiban el crecimiento de este microorganismo.…”
Section: Introductionunclassified
“…Lately, the major fluctuations have been observed in a protein [AFUA_1G12250] in mitochondria, whose intensity reduced more than 16 times in the secreted portion. Earlier studies revealed the probable importance of this protein as a biomarker exclusively to CAS as it was not reported while A. fumigatus was exposed to either voriconazole or AmpB [61][62].…”
Section: Latest Techniques For Multifactor Analysis Including Proteommentioning
confidence: 99%
“…Some enzymes catalyzing cell wall biosynthesis and the regulating BG synthase were also acknowledged [62].…”
Section: Latest Techniques For Multifactor Analysis Including Proteommentioning
confidence: 99%
“…Two-dimensional polyacrylamide gel electrophoresis (2D-PAGE) has been widely used for proteomic investigations of C. albicans [11,12]. 2D-PAGE has typically been used for protein separation for proteome analysis.…”
Section: Time-course Proteomic Analysis Of C Albicansmentioning
confidence: 99%